2017
DOI: 10.1371/journal.pone.0188561
|View full text |Cite
|
Sign up to set email alerts
|

Measuring couple relationship quality in a rural African population: Validation of a Couple Functionality Assessment Tool in Malawi

Abstract: Available data suggest that individual and family well-being are linked to the quality of women’s and men’s couple relationships, but few tools exist to assess couple relationship functioning in low- and middle-income countries. In response to this gap, Catholic Relief Services has developed a Couple Functionality Assessment Tool (CFAT) to capture valid and reliable data on various domains of relationship quality. This tool is designed to be used by interventions which aim to improve couple and family well-bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…First, it could indicate unmeasured benefits from support by one’s family in managing a shared latrine. Family-level support could reduce the likelihood of depressive symptoms in women, and therefore likelihood of PTB [ 57 , 58 ], or it could represent better marital relationships and better access to care [ 59 ] and a lower likelihood of domestic violence [ 60 ]. Second, women who relied on their community to resolve water problems may be an indicator of women living in communities with more water problems instead of an indicator of collective efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…First, it could indicate unmeasured benefits from support by one’s family in managing a shared latrine. Family-level support could reduce the likelihood of depressive symptoms in women, and therefore likelihood of PTB [ 57 , 58 ], or it could represent better marital relationships and better access to care [ 59 ] and a lower likelihood of domestic violence [ 60 ]. Second, women who relied on their community to resolve water problems may be an indicator of women living in communities with more water problems instead of an indicator of collective efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has found that unity was a key construct of power among young couples and a predictor of IPV and HIV-related health behaviours (Conroy 2014a;Conroy 2015;Conroy and Wong 2015). Similarly, previous research from Malawi found that shared decision-making was associated with positive relationship dynamics (e.g., intimacy, positive communication), whereas sole decision-making by women or men was associated with negative health behaviours and more IPV (Ruark, Chase et al 2017).…”
Section: Discussionmentioning
confidence: 83%
“…Mental health was assessed using the Patient Health Questionnaire (PHQ-9), a common depression screener that has been validated for use among pregnant women in Ghana (25). The PHQ-9 has nine items that are summed for a score between 0 and 27 and standard categorization: minimal or no depression (score of 0 to 4), mild depression (5-9), moderate depression (10 to 14), moderately severe depression (15)(16)(17)(18)(19), and severe depression (20)(21)(22)(23)(24)(25)(26)(27) (26). For analysis, we dichotomized the PHQ-9 into none to mild depression (score of less than 10) and moderate to extremely severe (score of 10 or greater), based on those who would have screened for no treatment or treatment in a clinical setting (25,27).…”
Section: Methodsmentioning
confidence: 99%